Peningkatan Literasi Sejarah Lokal dan Nilai Karakter melalui Pelatihan Penulisan Biografi Tokoh Daerah bagi Siswa MAN 1 Sanggau - Mahrus, Erwin; Sulistyowati, Dewi; Marniawarsih, Dayang; Abidah, Nur (Jurnal Pengabdian Kepada Masyarakat, 2025)
The Community Service Activity (PKM) in the form of Local Figure Writing Training was conducted by a team of IAIN Pontianak Postgraduate Students at MAN Sanggau with the aim of improving students' local history literacy and skills in writing biographies of regional figures. The training took place through material delivery, discussion, and direct practice involving biography writing techniques and oral history interviews. The results of the activity showed that students had a better understanding of inspirational figures in Sanggau Regency and the exemplary values they embodied. In addition, the training successfully developed the writing skills of the students and fostered positive characteristics such as curiosity, concern for local culture, and appreciation for the role of local figures. This activity also gave rise to the idea of forming a madrasah literacy community focused on documenting local figures. Overall, this PKM program was deemed effective and worthy of being developed as a sustainable activity for the preservation of local history and culture in the madrasah environment.